The Hasmoneans and their neighbors: new historical reconstructions from the Dead Sea Scrolls and classical sources - Atkinson, Kenneth (Jewish and Christian texts in contexts and related studies, 2018)
Cover -- Title -- Copyright -- Dedication -- Contents -- Acknowledgments -- Abbreviations -- Chapter 1: Introduction : The Sources and Their Limitations -- The Beginning of the Hasmonean State -- Sources for the History of the Hasmonean State: Josephus -- Sources for the History of the Hasmonean State: The Dead Sea Scrolls -- Sources for the History of the Hasmonean State: Classical Texts, Numismatics, and Other Literature -- Conclusion -- Chapter 2: The Early Hasmonean Period : New Evidence from the Dead Sea Scrolls -- The Origin of the Hasmonean Family's Revolt -- The Ptolemaic Rulers and the Hasmoneans -- Conclusion -- Chapter 3: Prophetic Messianism and Hasmonean State Expansion : Dangers from the Seleucid Empire -- Excursus 1: Demetrius II and the Decline of the Seleucid Empire -- The Mysterious Arrival of Antiochus VII Sidetes -- Hyrcanus and Antiochus VII Sidetes Invade the Parthian Empire -- How Did Hyrcanus Survive the Parthian Expedition of Sidetes? -- An Unknown Parthian War of Sidetes: Hyrcanus the Conqueror of Hyrcania -- Hyrcania and John Hyrcanus -- Turmoil to the North -- Hyrcanus as a Prophetic Messiah in the Dead Sea Scrolls -- Conclusion -- Chapter 4: The Creation of the Hasmonean Monarchy : Apocalyptic Expectations and the Dead Sea Scrolls -- Hasmonean Kings, High Priests, and the True Prophet -- The Deaths of Aristobulus and Antigonus -- Chapter 5: Religious Strife in the Hasmonean State : Foreign Threats, Ptolemaic Messianism, and the True Prophet -- Excursus 2: Numismatics and the Fratricidal Seleucid Wars in Antiquities 13.365-371 -- Egypt's Political Situation and the Jews -- Excursus 3: A Tarnished Reputation?: Ptolemy VII Physcon, His Wives, and a Ptolemaic Messiah -- Excursus 4: Egyptian Messianism in the Third Sibylline Oracle -- The Invasion of Demetrius III in the Dead Sea Scrolls